E-Jawi: Digital Learning Tool For Jawi Character Recognition - A.Rahim, Siti Nadzirah; Hamzah, Robiah (Journal of Computing Technologies and Creative Content, 2016)
Preschool education is one of the institutions which functions as a way to improve and further develop the understandings in all aspects of development for children aged 4 to 6 years old. Basic Jawi education is one of the aspects which is included in the Islamic education curriculum, set up by the Malaysian Ministry of Education Curriculum Development Centre. An application of media in teaching will be to diversify the skills of intelligence, which is absolutely necessary to acquire a skill. A proper technique needs to be used to make learning Jawi interesting. Hence, it is important to have suitable learning tools such as digital tools equipped with appropriate interactivity environment and proper interface design to aid children in developing an interest towards learning Jawi. In this work, the project named E-Jawi:Digital Learning Tool for Jawi Character Recognition was developed to help kindergarten students to explore learning jawi subject. The aim for this project is to be an interactive tool for learning how to write Jawi alphabets. In this paper, an approach for Jawi character recognition is proposed. The technique used in this project is grid baselines. The proposed technique is used sqlite database to store the coordinate for each Jawi alphabet and store the sequence of strokes. After reading the Jawi alphabets from user, the coordinates (x,y) of the pixels representing the drawn Jawi alphabets are used for calculating and normalizing slope values of these coordinates. This application has been tested on target users for its design appearance, learnability and capability to learners’ writing activities using computer. The results show that learners enjoy using the application for its design appearance. The application has also been proven to have a high learnability rate as users are able to use the application easily. In addition, it is also able to assist learners in mastering the Jawi writing exercise.